Analisis Daya Saing Ekspor Kopi Indonesia Di Pasar Internasional - Imamuddin Fathany; Didit Purnomo (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Indonesia is one of the largest coffee bean producing countries in the world. National coffee products have unique characteristics and flavors and are in demand in the global market. This makes coffee Indonesia's leading export product, so that the government will continue to strive to increase coffee exports from year to year so that coffee farmers can prosper and increase state income through coffee export activities. This study aims to analyze the effect of per capita gross domestic product, population, and exchange rate on the competitiveness of coffee exports to five countries (Germany, Italy, Japan, Malaysia, and the United States) where the five countries are the main destinations for Indonesian coffee exports. 2017-2021 years. The analytical tools used are Revealed Comparative Advantage and panel data regression. The results of the effect validity test using the selected model, namely Fixed Effects, show that per capita gross domestic product has a negative effect on the competitiveness of coffee exports. Meanwhile, the population and the exchange rate (exchange rate) in the export destination countries were found to have no effect on the competitiveness of Indonesian coffee exports. With the results of the research, the Indonesian government is expected to provide training and assistance to national coffee farmers so that the quality and quantity produced increases, so that national coffee products can be more competitive in the international market.